ATV/r+RAL (DT) after failure with NNRTI (Actualizaciones en Sida e Infectología, 2023)
Background: Dual therapy has emerged as a novel concept for HIV treatment. Thisstudy was aimed at comparing a nucleoside-sparing dual regimen consisting of ATV/r + RAL (DT) vs standard therapy of ATV/r + TDF/FTC (TT) among individuals failing first NNRTI-containing treatment.Methods: Randomized multicenter open-label pilot study. Primary outcome: proportion of subjects with plasma HIV-1 RNA below the limit of detection (
Keywords: Dual therapy; Atazanavir; Raltegravir; Second-line therapy; HIV experienced individuals; integrase resistance